The health effects of gendered and devalued work: health outcomes of incarcerated women engaging in sex work and care/service work - Sage J. Kim; Caryn Peterson (BMC, 2020)
Abstract Background Women with a history of incarceration are often engaged in highly gendered work, either sex work or low-wage care/service work jobs. While employment is an important element of reentry plans, low-wage jobs may not necessarily help women leave illicit activities, including commercial sex work. Incarcerated women often move between care/service work and sex work to supplement income, putting them at greater risk for negative health outcomes. Results Using survey data from 400 women detained in a large urban jail, we examined how incarcerated women's experience with sex work and low-wage care/service work affects four health-related outcomes: overall health concerns, clinical depression, regular drug use, and self-esteem. Of the survey participants, 24% engaged exclusively in sex work and 34% in care/service work. However, 41% of women held both sex work and care/service work jobs, prior to incarceration. Compared to women engaged in care/service work, a greater proportion of women engaged in sex work reported overall health concerns, clinical depression, and regular drug use. On the other hand, women in care/service work jobs exclusively reported lower levels of self-esteem than women engaging in sex work. Conclusions Many reentry programs emphasize the importance of employment for former inmates, and yet, job options for women detained in jail are often limited to low-wage care/service jobs, which do not necessarily provide adequate security to lift women's economic burdens. Consequently, many women with a history of incarceration may supplement their income with sex work to meet their basic economic needs. However, both of these highly gendered and devalued jobs may negatively affect health and wellbeing of women.